Functional farm household typologies through archetypal responses to disturbances. (February 2020) - Tittonell, P.; Bruzzone, O.; Solano-Hernández, A.; López-Ridaura, S.; Easdale, M.H.
Highlights: Methods to delineate functional farm household typologies are not abundant in the literature Social-ecological systems exhibit classifiable patterns in their responses to disturbances Archetype analysis allows revealing such patterns by focusing first on extremal rather than average cases Archetype analysis allows combining quali- and quantitative information and research methods to build functional typologies We illustrate this approach using household responses to droughts in northern Patagonia, Argentina Abstract: Methods to construct farm household typologies may differ in their approach but they share a common feature: they rely mostly on structural farm data. Methods to build functional typologies are far less abundant. Households or communities are complex social-ecological systems that often exhibit patterns in their response to disturbances (e.g., droughts, floods, price shocks, policy change). We propose building functional typologies – classifiable ´behaviours´ of rural actors – using archetype analysis to categorise such responses and identify salient behaviours. We illustrate this approach by examining the response of rural households to recurrent droughts in northern Patagonia, Argentina, as revealed by 23 in-depth interviews about perceptions and strategies concerning droughts. Using the algorithm from Mørup and Hansen (2012), and the corrected Akaike decision rule, we identified three archetypes (A–C) that represented three distinct aggregated responses of households to droughts. Archetype A presented variable degrees of resistance to droughts (production losses < 40%), avoidance and diversification, whereas archetype B exhibited tolerance (higher losses) and some degree of transformability (off-farm income). Archetype C farms exhibited high levels of vulnerability, if some degree of tolerance to high losses, but no real adaptive strategy to speak of. Such pattern could not have been identified through the more commonly used typology building methods such as using multivariate and clustering techniques. By allowing to combine qualitative and quantitative information, and to deal with a relatively small number of observations, archetype analysis appears as highly suitable to delineate functional farm household typologies.